A case of hyperprolactinemia in patient with metastatic breast cancer: clinical case presentation - L. K. Dzeranova; E. A. Pigarova; T. О. Vasilieva; O. V. Manchenko; V. P. Vladimirova (Опухоли женской репродуктивной системы)
The described clinical case illustrates the importance of careful medical care and follow-up for oncology patients which can prevent high degree of tumor dissemination in case of the disease progression and improve survival rate and quality of life.